Inquiry-Based Learning in Science: Mathematical Reasoning’s Support of Critical Thinking - Konstantinos T. Kotsis (Scientia Publica Media, 2025)
The evolution of educational paradigms toward inquiry-based learning (IBL) in science education has significantly altered pedagogical practices by emphasizing the necessity of active student participation in the learning process. Through questioning, research, and problem-solving, IBL invites students to investigate scientific phenomena, so promoting a closer knowledge retention and understanding. Integral to this approach is the function of mathematical thinking, which functions not only as a tool for quantitative analysis but also as a basic framework for critical thinking. Mathematical reasoning helps students organize their searches, efficiently analyze data, and come to reasonable conclusions. This interaction improves their ability to link mathematical ideas and scientific concepts, developing more advanced higher-order thinking abilities. Understanding how mathematical reasoning supports critical thinking within IBL will help curriculum development and teaching strategies in science education be much more informed as education progressively prioritizes integrating multidisciplinary approaches. In science education especially, IBL is especially helpful since it fits very nicely with the Next Generation Science Standards, which support student-centered learning environments that advance critical thinking and teamwork. IBL helps students develop critical skills, including analytical thinking and reasoning, by pushing them to create their own questions and search for answers through investigation. Moreover, including mathematical reasoning in IBL improves students’ problem-solving capacity by letting them approach challenging scientific questions with a strong methodological framework. IBL thus not only fosters curiosity but also provides the cognitive tools required for advanced learning in scientific fields.